A Note on the Theory of Rationing - Henderson, A. (Review of Economic Studies, 1947)
A Note on the Theory of Rationing A. Henderson A. Henderson Manchester Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 15, Issue 1, 1947, Pages 42–45, https://doi.org/10.2307/2295928 Published: 01 April 1947